Alexander Marakuev - the first Director of the Central Scientific Library of the Far Eastern Branch of the Russian Academy of Sciences - A. A. Khisamutdinov (Библиосфера, 2017)
In 2017 the Central Scientific Library of the Far Eastern Branch of the Russian Academy of Sciences (CSL FB RAS) in Vladivostok celebrates the 85th anniversary of its foundation. The publication uses rare materials from Vladivostok archives. CSL FBRAS formation was due to the enthusiastic orientalist A. V. Marakuev (1891-1955), who was its first Director (since 1932). Without a University degree, he educated himself the whole life, learnt Chinese and other foreign languages. During a trip around the world he lived in Harbin, where was engaged in scientific work. Arriving Vladivostok, Marakuev participated in opening the Far Eastern Branch of the USSR Academy of Sciences. At that time, he has published many articles on bibliography and economic geography of the Far East and Oriental studies. A. V. Marakuev awarded a degree of candidate of geographical sciences for a series of his works. In difficult years of repression, Marakuev could form a unique book collection, which base was the Oriental Institute collection in Vladivostok (1899-1920). Unfairly repressed A. V. Marakuev continued research activities in Alma-Ata.